Neuropsychological Correlates of Pre-Frailty in Neurocognitive Disorders: A Possible Role for Metacognitive Dysfunction and Mood Changes - Amanzio, Martina; Palermo, Sara; Zucca, Milena; Rosato, Rosalba; Rubino, Elisa; Leotta, Daniela; Bartoli, Massimo; Rainero, Innocenzo (Frontiers in Medicine, 2017)
Background: Recent studies have suggested that cognitive functions in patients with neurocognitive disorders have a significant role in the pathogenic mechanisms of frailty. Although pre-frailty is considered an intermediate, preclinical state, epidemiological research has begun to dislodge cognition and frailty into their specific subcomponents in order to understand the relationship among them. We aim to analyze the possible association between pre-frailty and neuropsychological variables to outline which factors can contribute to minor and major neurocognitive disorders. Methods: 60 subjects complaining of different cognitive deficits underwent a deep-in-wide frailty and neuropsychological assessment. We conducted 3 multiple linear regression analyses adjusted for a combination of demographic measures and involving several neuropsychological-behavioral parameters selected by the literature on physical frailty. Results: We found a significant association between frailty - as meaused by the Multidimensional Prognostic Index (MPI) – and action monitoring and monetary gain (cognitive domain), depression and disinhibition (behavioural domain). Moreover, an association between MPI and impaired awareness for instrumental activities disabilities exists. Conclusion: We propose a novel framework for understanding frailty associated with metacognitive-executive dysfunction.